The Legal Policy Framework for The Management of Development and Rural Spaces After The Entry into Force of The New No. 6 Year 2023 on The Establishment of Government Regulations to Replace The Law No. 2 Year 2022 on The Creation of Jobs to Become a Law - Muin, Fatkhul (Mahadi: Indonesia Journal of Law, 2024)
The spatial policy is a key instrument in creating the use of the spaces that exist in Indonesia, ranging from the level of central government, provincial government, district government to the village level. Spatial law policy, generally at the most basic level, where the village has a strategic role in the space management framework. In accordance with article 48 of the Act No. 6 of 2023 on the Establishment of Government Regulations to Replace the Law No. 2 of 2022 on the Creation of Works into Law, that the Rural Area Design is directed to: 1) empowerment of rural communities; 2) defence of the quality of local environment and the Territories supported by it; 3) conservation of natural resources; 4) preservation of local cultural heritage; 5) defense of perennial agricultural land for food sustainability; and 6) maintenance of the balance of rural-urban development. The basic concept of rural spatial planning is oriented towards the interests of empowerment of society. In this study analyzes related to the village spatial law policy in a legal perspective. By using normative law research.